2014
DOI: 10.5604/15093492.1119619
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure and Walking Speed in Lower Limb Amputees: a Cross Sectional Study

Abstract: 1. A higher level of amputation is associated with less energy-efficient walking and with lower walking speed. 2. Prosthetic ambulation supported with crutches has significant impact on increasing of energy expenditure and decreasing walking speed. 3. Stump length is shown to have a major impact on PCI and CWS in transfemoral amputees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 24 publications
1
15
0
19
Order By: Relevance
“…10 Fall prevention programs and home intervention may limit this risk, particularly in geriatric amputees. 29,30 In agreement with the literature, 5,6,31,32 transfemoral amputees presented higher prevalence of falls and lower walking speed, even when using more walking assistive devices. Different impairments in mobility (muscle strength, balance, etc.…”
Section: Discussionsupporting
confidence: 86%
“…10 Fall prevention programs and home intervention may limit this risk, particularly in geriatric amputees. 29,30 In agreement with the literature, 5,6,31,32 transfemoral amputees presented higher prevalence of falls and lower walking speed, even when using more walking assistive devices. Different impairments in mobility (muscle strength, balance, etc.…”
Section: Discussionsupporting
confidence: 86%
“…Given the fact that more than 50 studies were identified, studies with a sample size less of than 10 participants were excluded (n = 27). Two studies were found [36,37] that partially included the same study population (in one study persons with a Syme amputation were included and in the other study they were excluded). The former study was included in this study [36].…”
Section: Resultsmentioning
confidence: 99%
“…Stump length has been shown to have a significant impact on physiological cost index and comfort walking speed in transfemoral amputees [6]. This was a consideration that was weighted in the risk benefit assessment during the informed consent process in this patient.…”
Section: Discussionmentioning
confidence: 99%